Science Literacy among The Bachelor of Elementary Education Students at Osias Colleges Inc. - Anchiboy, Jeanne T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The purpose of this study was to investigate science literacy among the Bachelor of Elementary students at Osias Colleges Inc. The study employed a descriptive research design to describe science literacy among 50 students of Bachelor of Elementary Education. Science literacy was evaluated using indicators namely: recognizing scientific questions, identifying evidence, drawing conclusions, communicating conclusions, and demonstrating an understanding of scientific concepts. The results showed that the science literacy level of the students is described as “beginning”. In this regard, strategies and activities are proposed for each of the five science literacy indicators. Since the science literacy level of the BEED students is described as “beginning”, it is recommended that the College of Education should provide an entrance examination to first-year students particularly in the field of science education. Additionally, teachers should incorporate technology in learning to assist students who are struggling with science literacy and provide extra resources to help them improve their understanding of scientific concepts. The proposed strategies and activity cards may be implemented to raise the students science literacy level.